Clinical evaluation of total abdominal hysterectomy - a prospective study in a tertiary care hospital - Akhter, Shirin; Nazneen, Rumana (Northern International Medical College Journal, 2015)
Total abdominal Hysterectomy are gradually rising in our country. This study has been designed to find out the common indications of abdominal hysterectomy in a tertiary care hospital,. to know the clinical characters of the patients and. o elucidate postoperative complication of abdominal hysterectomy. Methodology : Cross- sectional observational study was done during 1st October 2007 to 30th September 2008. Holy Family Red Crescent Medical College Hospital (HFRCMCH). Total 100 patients were selected following enclusion & exclusion criteria hyperposive sampling. Data were recorded before and after operation and analyzed by SPSS version 15. Result : In the present study patients with leiomyoma of uterus was found to be the major indication of hysterectomy followed by dys functional uterine bleeding (DUB) 18.0%, Pelvic inflammatory disease (PID) 14.0%, chronic cervicitis 10.0%, adenomyosis 10.0%, pelvic endometriosis 6.0%, cervical polyp 2.0%, ovarian cysts 1.0% and chriocarcinoma 1.0%. Mean duration of operation (hour) and hospital stay was 1.15 hours and 7.48 days respectively. Most common complication of present series was fever 20.0% followed by 13.0% had wound infection, 6.0% UTI and 2.0% wound dehiscence. Conclusion : Hysterectomy is now the most widely performed major operation in gynaecology. Indication and post operative complications of hysterectomy varies from region to region. Northern International Medical College Journal Vol.6(2) 2015: 76-77